Tabanids: Neglected subjects of research, but important vectors of disease agents - Baldacchino, Frédéric; Desquesnes, Marc; Mihok, Steve; Foil, Lane D.; Duvallet, Gérard; Jittapalapong, Sathaporn (Infection, genetics and evolution, 2014)
•We provide a summary of tabanid morphology, biology and life cycle.•We highlight their medical and veterinary importance.•We discuss parameters of mechanical transmission and its mathematical modeling.•We summarize the control methods for tabanid populations and livestock protection.•We provide recommandations for the direction of future research. Tabanids are nuisance pests for people and livestock because of their painful and irritating bite, persistent biting behavior, and blood ingestion. About 4400 tabanid species have been described; they are seasonally present in all kinds of landscapes, latitudes, and altitudes. High populations have a significant economic impact on outdoor activities, tourism, and livestock production. Tabanids are also vectors of animal disease agents, including viruses, bacteria and parasites. However, tabanids have received little attention in comparison with other hematophagous Diptera. Here, we highlight the many direct and indirect impacts of tabanids and provide a brief summary of tabanid morphology, biology, and life cycle. Impacts include pathogen transmission, parasite transportation (Dermatobia hominis), biological transmission (Loa loa), and mechanical transmission of viruses, such as equine infectious anemia virus, protozoa, such as Trypanosoma evansi and Besnotia besnoiti, and bacteria, such as Bacillus anthracis and Anaplasma marginale. We discuss parameters of mechanical transmission and its mathematical modeling. Control methods for tabanid populations are also summarized; these include trapping, the use of insecticides, repellents, and livestock protection. Lastly recommendations are provided for the direction of future research.